Environmental Health Risk Analysis Due to Particulate Matter (PM10) on Workers at PT Diamond Alfa Propetindo, Gundu-Gundu Village, Mawasangka Tengah District, Central Buton Regency - Lisa Asrianti; Ramadhan Tosepu; Surya Cipta Ramadhan Kete (Lembaga Pengembangan Kinerja Dosen, 2025)
According to the ILO ( International Labour Organization ) factory workers in industrialized countries are affected by respiratory diseases (pneumoconiosis, silicosis and others) due to exposure to dust in the workplace. PM 10 in the air is the main parameter in air pollution originating from the use of transportation and increased industrial activity. The results of explosions from factories and vehicles entering and leaving the industry can pollute the air and produce pollutants and some workers at the PT Diamond Alfa Propetindo factory do not use personal protective equipment (PPE) masks so that there is possible pollution of particulate matter (PM 10 ) which is dangerous and causes health problems . This study aims to analyze environmental health risks due to Particulate Matter (PM 10 ), individual characteristics, risk level (RQ), and risk management. This study uses a descriptive observational method and Environmental Health Risk Analysis (ARKL). Respondent data collection techniques use total sampling and questionnaires. The results of PM 10 measurements that have been converted to a 10-hour measurement time at point 1 are 62.8 µg/m 3 , point 2 is 62.7 µg/m 3 , point 3 is 72.2 µg/m 3 and point 4 is 60.1 µg/m 3 and do not exceed the threshold value (NAB) of ambient air quality standards. The results of the RQ calculation obtained from 60 workers are RQ ≤ 1 which means they are not at risk of being exposed to PM 10 so they do not require risk management or risk control